Methods of identifying and assessing special performance in table tennis - Levushkin, S. P.; Barchukova, G. V.; Laptev, A. I. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
The paper presents the results of a study aimed at developing a methodology for determining the special performance in table tennis. The techniques are based on the use of standard specific loads, pulsometry and a light simulator. 4 tests of working capacity were developed and tested. Proposed standards for assessing the special performance of elite athletes in table tennis.